Hypervigilance to pain may predict the transition from subacute to chronic back pain: a longitudinal observational study - Zhang, Wen; Löffler, Martin; Usai, Katrin; Mišić, Mina; Nees, Frauke; Flor, Herta (Journal of pain research, 2025)
Evaluate whether incorporating additional psychological and social risk factors, beyond those captured by the Örebro Musculoskeletal Pain Questionnaire
Gesehen am 12.08.2025